2022
DOI: 10.1136/thoraxjnl-2021-217867
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of asthma on the development of obesity among adults: an international cohort study, ECRHS

Abstract: IntroductionObesity is a known risk factor for asthma. Although some evidence showed asthma causing obesity in children, the link between asthma and obesity has not been investigated in adults.MethodsWe used data from the European Community Respiratory Health Survey (ECRHS), a cohort study in 11 European countries and Australia in 3 waves between 1990 and 2014, at intervals of approximately 10 years. We considered two study periods: from ECRHS I (t) to ECRHS II (t+1), and from ECRHS II (t) to ECRHS III (t+1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
2
15
0
2
Order By: Relevance
“…Obesity and asthma are common illnesses that pose substantial risks to public health [1]. Social and environmental risk factors can contribute to the development of both diseases [2]. Recent studies have identified possible connections between these illnesses, which have seen parallel growth globally [2].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Obesity and asthma are common illnesses that pose substantial risks to public health [1]. Social and environmental risk factors can contribute to the development of both diseases [2]. Recent studies have identified possible connections between these illnesses, which have seen parallel growth globally [2].…”
Section: Introductionmentioning
confidence: 99%
“…Social and environmental risk factors can contribute to the development of both diseases [2]. Recent studies have identified possible connections between these illnesses, which have seen parallel growth globally [2]. Specifically, obesity has been linked to a higher risk for asthma, and 38% of Americans who have asthma at present also have obesity [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations